Analisis Semiotika Makna Pernikahan Beda Agama Pada Film Bajirao Mastani - Syifa Fauziah Syukur; fatmawati fatmawati (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2018)
Bajirao Mastani is a colossal film with an Indian background that explains the issue. This film is important and interesting to investigate because this film legalize the marriage of different religions, this certainly makes the researchers worried later Muslims will be affected after watching the movie because the message is contrary to the teachings of Islam. Based on the abo ve context, the purpose of this study is to answer the question of how the meaning of religious denominational marriage in a denotative, connotative and mythic way in Bajirao Mastani film by Sanjay Leela Bhansali. The theory used is the semiotics of Roland Barthes which is known by the theory of Two-Stage Signification (Two Order of Signification). This research uses qualitative descriptive method, with Barthes semiotic approach. The meaning of different religious marriages in the film Bajirao Mastani among them is a different religious marriage between Islam and Hinduism is prohibited (haram) by the scholars this is contained in the Fatwa Majelis Ulama Indonesia (MUI). Thus, the essence of marriage that aims to create happiness in married life will turn into a complicated marriage and many contradictions.